Product Quality Control Using Six-Sigma Method and Failure Mode and Effect Analysis at Core Board Purwakarta Company - Hady Sofyan; Afif Fawa Idul Fata; Nugraha, Riro fizri (Jurnal Teknologika, 2024)
PT. Papertech is a company engaged in manufacturing that produces core board type paper. The process of making core boards is a continuous process where every day the company always produces coreboards that are not just one type of core board. Given these problems, one way to minimize defective product rosters is to use the six sigma method analysis and failure mode and effect analysis. Research analysis using the six sigma method goes through several stages, namely the Define stage, which defines a general picture regarding the influence of the process on customer service. Meanwhile, at the Measure stage, namely Critical To Quality, Control Map and DPMO and sigma calculations for the 3 highest causes of defects, namely low plybond, low gsm, low cobb. The DPMO value in November 2023 is 450000 with a sigma value of 1.626, December 2023 is 422535 with a sigma value of 1.695, January 2024 is 474934 with a sigma value of 1.563, February 2024 is 560000 with a sigma value 1,349, March in 2024 it will be 540,000 with a sigma value of 1,400. The Analyze stage is to determine the main cause of the defect using fishbone. The Improve stage is to make improvements using Failure Mode and Effect Analysis (FMEA) according to the highest Risk Priority Number (RPN) value level of 540 for material, 189 for machine, 540 for human and 61 for method. The Control stage is documenting the quality improvement results stage